Immune cytopenias as a continuum in inborn errors of immunity: An in‐depth clinical and immunological exploration. Issue 2 (10th April 2021) - Zama, Daniele; Conti, Francesca; Moratti, Mattia; Cantarini, Maria E.; Facchini, Elena; Rivalta, Beatrice; Rondelli, Roberto; Prete, Arcangelo; Ferrari, Simona; Seri, Marco; Pession, Andrea
Abstract: Background: Immune thrombocytopenia (ITP), autoimmune hemolytic anemia (AIHA), and autoimmune neutropenia (AIN) are disorders characterized by immune‐mediated destruction of hematopoietic cell lineages. A link between pediatric immune cytopenias and inborn errors of immunity (IEI) was established in particular in the combined and chronic forms. Objective: Aim of this study is to provide clinical‐immunological parameters to hematologists useful for a prompt identification of children with immune cytopenias deserving a deeper immunological and genetic evaluation. Methods: We retrospectively collected 47 pediatric patients with at least one hematological disorder among which persistent/chronic ITP, AIHA, and AIN, aged 0–18 years at onset of immune cytopenias and/or immune‐dysregulation. The cohort was divided into two groups (IEI+ and IEI−), based on the presence/absence of underlying IEI diagnosis. IEI+ group, formed by 19/47 individuals, included: common variable immune deficiency (CVID; 9/19), autoimmune lymphoproliferative syndrome (ALPS; 4/19), DiGeorge syndrome (1/19), and unclassified IEI (5/19). Results: IEI prevalence among patients with ITP, AIHA, AIN, and Evans Syndrome was respectively of 42%, 64%, 36%, and 62%. In IEI+ group the extended immunophenotyping identified the presence of statistically significant ( p < .05) specific characteristics, namely T/B lymphopenia, decrease in naїve T‐cells%, switched memory B‐cells%, plasmablasts%, and/or immunoglobulins, increase in effector/central memory T‐cells% and CD21low B‐cells%. Except for DiGeorge and three ALPS patients, only 2/9 CVID patients had a molecular diagnosis for IEI: one carrying the pathogenic variant CR2:c.826delT, the likely pathogenic variant PRF1:c.272C> and the compound heterozygous TNFRSF13B variants p.Ser144Ter (pathogenic) and p.Cys193Arg (variant of uncertain significance), the other one carrying the likely pathogenic monoallelic variant TNFRSF13B:p.Ile87Asn. Conclusion: The synergy between hematologists and immunologists can improve and fasten diagnosis and management of patients with immune cytopenias through a wide focused clinical/immunophenotypical characterization, which identifies children worthy of IEI‐related molecular analysis, favouring a genetic IEI diagnosis and potentially unveiling new targeted‐gene variants responsible for IEI phenotype. Abstract :